Factors that affect public relations practice: in the case of Tigray Education Bureau - Mulu, Solomon Shiwabaw (Technium Social Sciences Journal, 2020)
Public relations practice is a profitable interpretation of an organization's new and continuous relationship with stakeholders, including customers, by managing all communication relationships with the organization that creates the reputation and protects its reputation [5]. The researcher has employed mixed research methods. Mixed approaches are far more compressive than attacking a problem one point of view and allow a different type of data to be accessed from disciplinary boundaries. Employing a purposive sampling method, a total of 7 PR officers of the Tigray region education Bureau and the Public relations Manager of the respective Bureau have been selected. An interview and questionnaires have been employed to gather data. After the researcher has collected the relevant data using the mixed research methods it has been analyzed. The data which was gathered using a quantitative research method has been analyzed and interpreted in a table and report in percentage with sufficient explanation for each table result and percentages using SPSS data analyzing software. Besides, the gathered data using a qualitative research design was analyzed in the reporting method with elaboration.